Peningkatan Aktivitas Dan Hasil Belajar Matematika Melalui Model Pembelajaran Berdasarkan Masalah (Problem Based Learning) Pada Peserta Didik Kelas VI SDN 04 Nan Sabaris Tahun Pelajaran 2015/2016 - Effendi M (Jurnal Konseling dan Pendidikan, 2016)
Initial observation shows that there are some problems that teachers face in mathematics learning. One of those problems is difficulty in encouraging student about the understanding concept of proposition and scale. This research is aimed to improve student’s learning activiy and output in learning mathematics by implementing problem based learning model. This is classroom action research with subject are students grade VI SDN 04 Nan Sabaris. Data were obtained through observation on student’s participation in learning, observation on teacher’s activities, and final test for students. Data were analyzed quantitatively and qualitatively. Hasil analisis data diketahui bahwa aktivitas belajar siswa meningkat. Based on the result of this research, percentage of student’s activity in learning is 66.19% for cycle I and 81.90% for cycle II. Thus, implementation of problem based learning in learning mathematics can improve student’s learning activity and output.